Synthesis of CdS and CdSe nanoparticles by thermolysis of diethyldithio- or diethyldiseleno-carbamates of cadmium - Trindade, Tito (2012)
Cadmium sulfide and cadmium selenide nanoparticles have been synthesised by a novel route involving the thermal decomposition of the bisdiethyldithio- or bisdiethyldiseleno-carbamates of cadmium in refluxing 4-ethylpyridine solutions. The nanodispersed materials were studied by electronic spectroscopy and bandgaps were blue shifted. Transmission electron microscopy of the samples showed material to be in the nanosize range and crystalline.